2016
DOI: 10.1016/j.atmosenv.2016.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fine and carbonaceous particles emissions from pelletized biomass-coal blends combustion: Implications on residential crop residue utilization in China

Abstract: h i g h l i g h t sEmissions of PM 2.5 , OC and EC from biomass pellets were lower than bulk materials. High thermal efficient stoves reduce emissions from pelletized biofuel. Pelletized biomass and coal blends could significantly decrease emissions. a r t i c l e i n f o Bulk biofuel, biomass pellets and pelletized biomass-coal blends were combusted in a typical rural conventional household stove and a high-efficiency stove. Reductions in PM 2.5 , organic carbon (OC) and elemental carbon (EC) emissions were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 29 publications
(48 reference statements)
0
4
1
Order By: Relevance
“…Sun et al also reported that the briquetting of an anthracite chunk led to an increase in organic carbon EFs of over eight times that of the anthracite chunk . In addition, some studies have shown that biocoal briquettes (coal and biomass blend) can increase modified combustion efficiency (MCE) and decrease pollutant releases because of the synergy between coal and biomass. , Conversely, in this study, coal-biomass blend fuel emitted higher emissions than coal briquettes alone. EFs for carboxylic acids from bituminous–biomass blend fuel and anthracite–biomass blend fuel were 1.1 and 5.1 times higher than those from bituminous and anthracite briquette.…”
Section: Resultscontrasting
confidence: 73%
“…Sun et al also reported that the briquetting of an anthracite chunk led to an increase in organic carbon EFs of over eight times that of the anthracite chunk . In addition, some studies have shown that biocoal briquettes (coal and biomass blend) can increase modified combustion efficiency (MCE) and decrease pollutant releases because of the synergy between coal and biomass. , Conversely, in this study, coal-biomass blend fuel emitted higher emissions than coal briquettes alone. EFs for carboxylic acids from bituminous–biomass blend fuel and anthracite–biomass blend fuel were 1.1 and 5.1 times higher than those from bituminous and anthracite briquette.…”
Section: Resultscontrasting
confidence: 73%
“…From this perspective-and because biomass torrefaction is a technology that enables the standardization of different types of biomass, thus allowing the use of a wider range of plant Sustainability 2020, 12, 922 5 of 9 species-biomass torrefaction could also play a key role in the eradication and control of invasive species, which may be classified as a resource, but also by the contribution to the clearing of the forest space, specifically in the elimination of residues resulting from forestry operations [54,55]. Thus, the production of energy products does not conflict with the market for raw materials for other industries, namely pulp and paper and wood pellets, and also contributes to reducing the risk of forest fires by decreasing the permanent fuel load [56,57].…”
Section: Forest Management From the Supply Of Biomass To Energy Perspmentioning
confidence: 99%
“…Though from the experiences in developed countries, those compressed biomass fuels may have the potential to reduce emissions of PICs and consequently to improve air quality, which is important for the population heavily relying on traditional solid fuels from rural developing countries, emission experiments on PIC emissions from biomass pellets in residential stoves in developing countries are very limited. It was reported that pelletized biofuels could significantly reduce PM 2.5 , OC, EC, CO, and PAH emissions, with reduction rates up to more than 90% compared with ordinary raw biomass. However, a few results showed insignificant changes, or even higher, in emissions of hazardous pollutants like ultrafine particles, PAHs, and their derivatives. For example, it wasreported that emission factors (EFs) of PAH from wood pellets were much lower and accounted for only 19% of the EFs from firewood, while another study revealed that PAHEFs for pine wood pellets averaged at 0.67 mg/MJ, which was higher than that for pine wood at 0.34 mg/MJ . Meanwhile, while changes in the mass of these compounds are discussed, there is growing concern about how particle toxicity changed when the physiochemical properties of the particles were distinct.…”
Section: Introductionmentioning
confidence: 99%